ANALISIS PENGARUH TINGKAT SUKU BUNGA, INFLASI, DAN NILAI TUKAR TERHADAPFOREIGN DIRECT INVESTMENT DI INDONESIA - Elsa, wulandari; Wirati, Adriati (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT The main purpose of this research is to analyze the effect of interest rate, inflation, and exchange rate on Foreign Direct Investment (FDI) in Indonesia. Data obtained in this research is secondary data from the years 2010-2015, which is accessed through the website  www.bkpm.go.id and  www.bi.go.id. Data analysis techniques used in this research is descriptive analysis, classic assumption test, multiple linear regression analysis, and the coefficient of determination (R2). The result of this research indicate that interest rate with a regression coefficient -46,571 and a significance level 0,807 greater than 0,05 which means the interest rate had no significant effect on FDI in Indonesia, inflation has a regression coefficient -146,704 with a significance level 0,021 smaller than 0,05 which means inflation had significant negative effect on FDI in Indonesia, the exchange rate has a regression coefficient -0,178 with a significance level 0,015 less than 0,05 which means that the exchange rate also had significant negative effect on FDI in Indonesia, and interest rate, inflation, and exchange rate has a significant effect on FDI in Indonesia simultaneously with the F count > F table that is 34,021 > 2,74 or the Sig. F (0,000) < a = 0,05